2010
DOI: 10.1016/j.ijpharm.2010.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of acyclovir and its squalenoyl–acyclovir prodrug with DMPC in monolayers at the air/water interface

Abstract: a b s t r a c tAcyclovir has been conjugated to the acyclic isoprenoid chain of squalene to form the squalenoyl-acyclovir prodrug. Its interaction with biomembrane models constituted by dimyristoylphosphatidylcholine (DMPC) monolayers has been studied by employing the Langmuir-Blodgett technique. The aim of the work was to gain information on the interaction of these compounds with phospholipid membranes.DMPC/acyclovir or squalenoyl-acyclovir prodrug mixed monolayers have been prepared at increasing molar frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Langmuir monolayers are also usually used for investigating amphiphilicity and possible interaction between amphiphiles [8,9]. Some important information about the molecular configurations of amphiphiles can be predicated according to their monolayer behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Langmuir monolayers are also usually used for investigating amphiphilicity and possible interaction between amphiphiles [8,9]. Some important information about the molecular configurations of amphiphiles can be predicated according to their monolayer behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that esterases are present in several ocular structures, and their activity is the main factor responsible for the bioreversion of amino acid prodrugs of acyclovir [19], [39] and [42]. Our study employed a lipophilic prodrug of ACV, obtained by conjugation with 1,1′,2-trisnorsqualenoic acid, as has been proposed by Sarpietro et al [33] and [43]. In particular, Sarpietro et al highlighted the fact that the formation of a lipophilic prodrug gives rise to a stronger interaction with the biomembrane model and is absorbed in larger quantities by the biomembrane model constituted by dimyristoylphosphatidylcholine, than 1,1′,2-trisnorsqualenoic acid [33] and [43].…”
Section: Discussionmentioning
confidence: 94%
“…Our study employed a lipophilic prodrug of ACV, obtained by conjugation with 1,1′,2-trisnorsqualenoic acid, as has been proposed by Sarpietro et al [33] and [43]. In particular, Sarpietro et al highlighted the fact that the formation of a lipophilic prodrug gives rise to a stronger interaction with the biomembrane model and is absorbed in larger quantities by the biomembrane model constituted by dimyristoylphosphatidylcholine, than 1,1′,2-trisnorsqualenoic acid [33] and [43]. The results reported by Sarpietro et al using differential scanning calorimetry (DSC) analysis [33] indicated that 1,1′,2-trisnorsqualenoic acid and SQACV had a fluidizing effect on the phospholipid bilayer, interacting with the hydrophobic acyl chains, while acyclovir does not enter the phospholipid bilayers [44].…”
Section: Discussionmentioning
confidence: 99%
“…The squalenoylation technology was also extended to develop a new ester prodrug with antiviral activity, squalenoyl-acyclovir (Sq-ACV). The interaction of Sq-ACV with biomembrane models made of DMPC MLV was studied by means of DSC and LB techniques [62,63]. The DSC study concerned the effects of ACV and of Sq-ACV towards the liposomal biomembranes (MLV) [62].…”
Section: ) Squalene-derived Nanoparticlesmentioning
confidence: 99%